Enacting and capturing embodied knowledge in the practices of enthusiast car restorers: Emerging themes. (December 2019) - Lloyd, Annemaree; Olsson, Michael
This paper reports on emerging themes drawn from a larger ongoing qualitative study of car restorers which explores themes of embodiment, embodied knowledge and ways of knowing. The themes described in this current article indicate that car restoration is bounded within a discourse of loyalty to the particular type of practice and its projects (restoration), its material object (the car) and to narratives of expertise, maintenance and preservation. The study's findings also demonstrate that enthusiast car restorers, along with other serious leisure communities, have become the unacknowledged custodians of a large body of hands-on knowledge which would otherwise be in danger of being lost in an increasingly post-industrial world.